The Severity of diabetic retinopathy and its relationship with duration of diabetes and hypertension - Preethi K S; Suresh Devatha (International Journal of Medical Research and Review, 2024)
Objective: This study aims to evaluate the risk factors affecting diabetic retinopathy and its severity in type 2 diabetic patients about the duration of diabetes and hypertension.Methods: A retrospective chart analysis was done of patient data collected from the patients visiting our tertiary institute (Karnataka Institute of Endocrinology and Research) from November 1st, 2022 to October 31st, 2023. In these diabetic patients, the prevalence of diabetic retinopathy and its severity concerning the duration of diabetes and hypertension was evaluated. Diabetic retinopathy and diabetic macular edema (DME) were classified based on the International Clinical Disease Severity Scale for Diabetic Retinopathy (DR).Result: 5363 was the total number of diabetic patients included in this study. The prevalence of Diabetic retinopathy(DR) was 13.95% with diabetes for less than 5 years, 37% with diabetes for 5 to 10 years and 58.74% for more than 10 years. In diabetic patients with associated hypertension, the prevalence of diabetic retinopathy (DR) was 36 % as compared to 28.4% without associated hypertension. In multivariate analysis for factors associated with diabetic retinopathy, the odds ratio (OR) was 3.61% (95% CI, 3.08 – 4.23, P – Value < 0.001) in patients with diabetes between 5 – 10 years and in patients with diabetes above 10 years the odds ratio (OR) was 8.69 (95% CI, 7.36 – 10.26, P – Value < 0.001) as compared to patients with diabetes < 5 years. The odds ratio (OR) for developing DR was 1.19 (95% CI, 1.03 – 1.37, P – Value 0.015) in patients with diabetes and hypertension as compared to diabetic patients without hypertension.Conclusion: The prevalence of diabetic retinopathy is higher in diabetic patients with longer duration of diabetes and diabetic patients with associated hypertension. It is important to evaluate all diabetic patients for diabetic retinopathy and maintain good glycemic and hypertensive control. Managing comorbidities along with diabetes reduces the prevalence and complications of diabetic retinopathy.